A perception study of an integrated water system project in a water scarce community in the Philippines - Ignacio, Jonathan Jared J. (Animo Repository, 2019)
© 2019 by the authors. The Integrated Water System (IWS) offers alternative water and sanitation services that can potentially benefit rural communities experiencing water scarcity. The IWS described in this study comprises three systems: The Rainwater Harvesting System (RWHS), Water Treatment System (WTS), and Eco-Toilet System (ETS). RWHS and WTS make use of rainwater, which can be utilized for several domestic uses, especially during wet season. ETS has several benefits to users including promotion of environmental and public health, as well as food security. Despite the potential benefits of the IWS components, the perceived acceptance of its users threatens the success of its implementation. This study focuses on determining the significant factors that can influence the social acceptance of IWS in the Municipality of Mulanay, Quezon Province, Philippines. This study considers behavioral intention as an indicator of social acceptance of the IWS components. The framework of this study is based on the combined technology acceptance model and theory of planned behavior (C-TAM-TPB) concept. C-TAM-TPB was analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The result of the C-TAM-TPB evaluation reveals that the user's attitude towards use (ATU), including its significant predictors, can promote behavioral intention towards use of the IWS components. This study can further improve the development of IWS projects.